Network effects on migrants' remittances - Ainhoa Aparicio Fenoll (Institute for the Study of Labor (IZA), 2011)
This paper explores the existence of network effects in migrants' remittance behavior. In this study, networks are defined as groups of immigrants from the same country that live in the same locality. Using the National Immigrant Survey, a unique database for Spain, immigrants are found to be more likely to remit and to remit more money if they belong to high remitting country groups. This finding sheds new light on the determinants of the decision to remit, as well as on the scope of immigrant networks.
urn:nbn:de:101:1-201104283125
Keywords: J61; F22; O15; A14; E21; 330; immigrant networks; remittances; Spain; Migranten; Soziales Netzwerk; Rücküberweisung (Migranten); Spanien